Synthesis of a Calcium Silicate Cement Containing a Calcinated Strontium Silicate Phase - Saeede Zadsirjan; Negar Parvaneh Dehkordi; Soolmaz Heidari; Farhood Najafi; Nazanin Zargar; Mojgan Feli; Sepideh Salimnezhad (International Journal of Dentistry)
Objectives. The positive effects of strontium on dental and skeletal remineralization have been confirmed in the literature. This study aimed to assess the properties of a calcium silicate cement (CSC) containing a sintered strontium silicate phase. Materials and Methods. The calcium silicate and strontium silicate phases were synthesized by the sol–gel technique. Strontium silicate powder in 0 (CSC), 10 (CSC/10Sr), 20 (CSC/20Sr), and 30 (CSC/30Sr) weight percentages was mixed with calcium silicate powder. Calcium chloride was used in the liquid phase. X-ray diffraction (XRD) of specimens was conducted before and after hydration. The setting time and compressive strength were assessed at 1 and 7 days after setting. The set discs of the aforementioned groups were immersed in the simulated body fluid (SBF) for 1 and 7 days. The ion release profile was evaluated by inductively coupled plasma-optical emission spectrometry (ICP-OES). Biomineralization on the specimen surface was evaluated by scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM/EDS). Data were analyzed by the Kolmogorov–Smirnov test, one-way and mixed ANOVA, Levene’s test, and LSD post hoc test (P <0.05). Results. Except for an increasement in the peak intensity of hydrated specimens, XRD revealed no other difference in the crystalline phases of hydrated and nonhydrated specimens. The compressive strength was not significantly different at 1 and 7 days in any group (P >0.05). The setting time significantly decreased by an increase in percentage of strontium (P <0.05). Release of Ca and Si ions significantly decreased by an increase in percentage of strontium (P <0.05). SEM/EDS showed the formation of calcium phosphate deposits at 1 and 7 days. Conclusion. Incorporation of 10−30 wt% sintered strontium silicate phase as premixed in CSC can significantly decrease the setting time without compromising the compressive strength or biomineralization process of the cement.